Guiding Inspiratory Flow: Development of the In-Check DIAL G16, a Tool for Improving Inhaler Technique - Sanders, Mark Jeremy (Pulmonary Medicine, 2017)
Portable inhalers are divisible into those that deliver medication by patient triggering (pMDIs: a gentle slow inhalation) and those that use the patient’s inspiratory effort as the force for deaggregation and delivery (DPIs: a stronger deeper inspiratory effort). Patient confusion and poor technique are commonplace. The use of training tools has become standard practice, and unique amongst these is an inspiratory flow meter (In-Check) which is able to simulate the resistance characteristics of different inhalers and, thereby, guide the patient to the correct effort. In-Check’s origins lie in the 1960s peak expiratory flow meters, the development of the Mini-Wright peak flow meter, and inspiratory flow assessment via the nose during the 1970s–1980s. The current device (In-Check DIAL G16) is the third iteration of the original 1998 training tool, with detailed and ongoing assessments of all common inhaler resistances (including combination and breath-actuated inhaler types) summarised into resistance ranges that are preset within the device. The device works by interpolating one of six ranges with the inspiratory effort. Use of the tool has been shown to be contributory to significant improvements in asthma care and control, and it is being advocated for assessment and training in irreversible lung disease.